(untitled) (Maneggio, 2025)
This study aims to analyze effective human resource management (HRM) strategies for building championship teams in the midst of globalization and digitalization. With the intensifying global business competition, companies are required to have resilient, adaptive, and competitive teams. This research explores the application of competency-based HR strategies, strategic recruitment, continuous training, and transformational leadership as key factors in shaping high-performing teams. In addition, the study highlights the importance of a collaborative organizational culture and the utilization of HR technology in managing human resources. The findings show that multinational companies tend to adopt modern HR strategies more rapidly compared to local companies, which often face challenges such as limited resources and resistance to change. This research suggests that companies implement more integrated and adaptive HR strategies to achieve competitive advantage and build outstanding teams.